Who Wants to be Legible? Digitalization and Intergroup Inequality in Kenya - Lisa Garbe; Nina McMurry; Alexandra Scacco; Kelly Zhang (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2023)
Governments across the Global South have begun introducing biometric IDs (eIDs) in an attempt to improve citizen-state legibility. While such initiatives can improve government efficiency, they also raise important questions about citizen privacy, especially for groups with a history of mistrust in the state. If concerns about increased legibility produce differential eID uptake or changes in political behavior, eID initiatives may exacerbate societal inequalities. In a conjoint experiment with 2,073 respondents from four Kenyan regions, we examine how perceptions of and willingness to register for eID under different policy conditions vary across politically dominant, opposition, and "securitized" (heavily policed) ethnic groups. Our results indicate broad support for expanded legibility, with respondents across groups preferring policies that link eIDs with a range of government functions. However, we find meaningful group-level variation in support for specific policy features, and suggestive evidence that policies facilitating greater surveillance may discourage opposition political participation.
Keywords: 320; Legibility; Surveillance; Digitalization; Kenya; Political Inequality; Ethnic Politics